Chaetomium, Chlonostachys, and Pseudogymnoascus isolates from tomato tissues significantly suppress Phytophthora infestans in tomato - Philemon Orwa; Theresa Kuhl-Nagel; Rosa Meinhold-Ernst; Arne Seyer; Johannes A. Jehle; Romano Mwirichia; Ada Linkies (PLoS ONE, 2025)
Late blight is a disease whose causative agent is the oomycete Phytophthora infestans. It is one of the most destructive pathogenic oomycetes and a major challenge to global tomato production. The pathogen is difficult to manage because of its ability to evolve thereby evading host resistance. The aim of this study was to screen for potential antagonists of P. infestans using a combination of culture and microbiome-based approaches. Samples were collected from healthy and P. infestans -infected tomato plants grown in soil collected from two organic tomato growers in the Rhine-Main area in Germany. A total of 246 fungal isolates were screened for their antagonistic activity against P . infestans . Most of the isolates that exhibited in vitro antagonistic activity were from the genera Penicillium, Trichoderma, Chlonostachys, Mortierella, and Pseudogymnoascus . Following a stepwise in vitro screening strategy that accounted for growth features, ecological aspects, taxonomic data, potential health risks, commercial properties, and antagonistic efficacy, five fungal isolates were eventually selected for plant trials. Chaetomium subaffine showed the highest inhibitory effect against P. infestans across three trials whereby the percentage of diseased leaf area reduced by 90% compared to the control. Chlonostachys and Pseudogymnoascus spp. were effective in two trials, while Trichoderma and Ctenomyces spp. showed weak disease suppressive effects. In parallel, we characterized the fungal microbiome of the rhizosphere, phyllosphere, and endosphere from healthy and diseased tomato plants using ITS-rRNA sequencing. The fungal community differed significantly between the two soil origins, but P. infestans did not significantly influence fungal microbiota composition. Notably, 70% of our antagonistic fungi from the culture collection were detected in the tomato microbiome. This work identified isolates of Chaetomium subaffine, Clonostachys sp., and Pseudogymnoascus sp. as potential biocontrol candidates promoting plant health. The findings highlight the importance of combined functional screening and microbiome profiling for identifying fungal antagonists.